2015
DOI: 10.7314/apjcp.2015.16.15.6279
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Atractylodes lancea (Thunb.) DC in a Hamster Model and Application of PET-CT for Early Detection and Monitoring Progression of Cholangiocarcinoma

Abstract: Opisthorchis viverrini (OV)-induced cholangiocarcinoma (CCA) is an important cancer in the Great

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Comparable anti-CCA activity and inhibitory activity on lung metastasis were also observed with BE. 19 In the hamster model, the promising anti-CCA activity of AL was observed at all dose levels, particularly at the highest oral dose level of 5,000 mg/kg body weight for 30 days. The median survival time was significantly prolonged (about two times) in mice treated with the extract at all dose levels compared with 5-FU treated and untreated control groups.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Comparable anti-CCA activity and inhibitory activity on lung metastasis were also observed with BE. 19 In the hamster model, the promising anti-CCA activity of AL was observed at all dose levels, particularly at the highest oral dose level of 5,000 mg/kg body weight for 30 days. The median survival time was significantly prolonged (about two times) in mice treated with the extract at all dose levels compared with 5-FU treated and untreated control groups.…”
Section: Discussionmentioning
confidence: 88%
“…The median survival time was significantly prolonged (about two times) in mice treated with the extract at all dose levels compared with 5-FU treated and untreated control groups. 19 Altogether, results suggest that the three major compounds in the AL rhizomes play an important role in the anti-CCA activity of AL. The study supports synergistic interaction of the active ingredients observed in all animal models.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations